Italia, Russia e mondo slavo Studi filologici e letterari - Di Salvo, Maria Giovanna (Biblioteca di Studi Slavistici, 2011)
This book is a collection of some of the most interesting work by Maria Di Salvo compiled on the occasion of her sixty-fifth birthday. These articles reflect her intellectual curiosity, her clarity of exposition and the capacity to apply and amalgamate different methodologies and disciplines, blending them into a coherent whole despite the variety of topics and subjects of study. We have favoured the essays that are harder to get hold of, making selections that enable the identification of two essential groups: the philological and literary studies and those related to the relations between Russia and Italy. We trust that the choices made will offer an organic overview of the intellectual and academic career of Maria Di Salvo, including the latest 'new path' of research, that on punctuation in the Slavic languages, and while awaiting the imminent publication by Edizioni dell'Orso, of the part devoted to Russia in the memoirs of Filippo Balatri, the famous castrato sent by the Grand Duke of Tuscany to the Russian court at the end of the seventeenth century.